A mixed acid treatment for the prevention of Ulva prolifera attachment to Neopyropia aquaculture rafts: Laboratory experimentation. (November 2022) - Sun, Yuqing; Xia, Zhangyi; Cao, Xiaoli; Tong, Yichao; He, Ruyan; Fu, Meilin; Sun, Jingyi; Xu, Hong; Xia, Jing; Liu, Jinlin; Kim, Jang Kyun; Zhang, Jianheng; et al.
Abstract: The sessile green macroalgae in the Neopyropia aquaculture areas of the Subei Shoal are a confirmed source of green tides in the Southern Yellow Sea (SYS) of China. The green tides have a significant impact on local economic development (tourism, aquaculture, etc.) and ecological stability. In order to develop an effective method for eliminating the green macroalgae attached to Neopyropia aquaculture rafts, this study investigated the effects of mixed acid solutions (0.0475 % hydrochloric acid [HCl] and pH 2.0 citric acid) on cell damage, chlorophyll composition, phycobiliprotein content, and the photosynthetic fluorescence characteristics of Ulva prolifera and Neopyropia yezoensis . The chlorophyll contents of U. prolifera and N. yezoensis were significantly affected by the mixed acid solutions. After treatment with a mixed acid solution (4:3 volume ratio of HCl to citric acid) for 5 s, the photosynthetic pigment content of U. prolifera was significantly different from that of normal U. prolifera . However, photosynthetic pigment content in the treated N. yezoensis increased significantly. In addition, mixed acid solution treatment had a significant effect on the Fv/Fm of U. prolifera and N. yezoensis . After mixed acid treatment (4:3 HCl to citric acid), U. prolifera completely died, but the Fv/Fm of N. yezoensis was restored after 3 d. Therefore, a mixed acid solution comprising 0.0475 % HCl and pH 2.0 citric acid (at a volume ratio of 4:3) can be used as an agent for the removal of green macroalgae from Neopyropia aquaculture areas. Graphical abstract: Unlabelled Image Highlights: An effective method was developed to eliminate green tide macroalgae. Ulva prolifera was completely killed with a mixed acid (4:3 HCl to citric acid). Neopyropia yezoensis treated with the mixed acid recovered after 3 days.